STRATEGI SOSIALISASI POLITIK KEPALA DESA DALAM PEMENANGAN PEMILIHAN KEPALA DESA BERBASIS PENGUATAN KEARIFAN LOKAL - Nike Purnamawati; Erinda Alfiani Fauzi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
In the 2022 Village Head Pilkada, the Mandastana City Village Apparatus did not focus its political outreach efforts on village community voters, even though the number of village community voters reached more than half of the votes. The village apparatus of Mandastana City decided that in the 2022 Pilkada, village community voters would become one of the strategic groups on the political socialization agenda. The large number of village community voters can be an opportunity for the Puntik Dalam Village apparatus to increase the percentage of voter participation in the 2022 Pilkada by conducting political socialization focused on the village community voter segment, with the hope of a large number of voters. Village community voters will encourage a significant increase in the percentage of voter turnout. Puntik Dalam Village, Mandastana Barito Kuala District, which has high cultural values, is actually not difficult to find and identify various local wisdoms that support village communities because many religious leaders and traditional elders can develop local wisdom. like songs, sayings, or even advice attached to everyday life. The village community, which is mostly made up of members of the indigenous Banjar tribe, has developed certain patterns of behavior and a set of core values over time. These patterns of behavior and values represent the local wisdom of the hamlet. Even though many migrants come from Javanese or Bugis tribes, villagers are still able to mingle and compete in a healthy manner in village head elections. Regarding the context of village head elections, because the use of this network media does not target certain groups of voters in particular, everyone can obtain election information and the 2022 Mandastana Regency Pilkada stages by using this network media, and are not constrained by space or time constraints for candidate heads village in carrying out its political winning strategy